Plant essential oils and their effectiveness against Musca domestica LINNAEUS, 1758 and its parasitoids - Mahyar Kimiaei,; Alireza Jalali Zand,; Esmaeil Mahmoodi,; Masih Razmjoo, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Pests and vector insects cause a great deal of economic and health disruption. Insect resistance and bioaccumulation are major disadvantages of the chemical control methods used against this pest. We investigated the larvicide and inhibition effect of Citrus sinensis (L.) Osbeck and Mentha pulegium Linnaeus essential oils against larvae and pupae of the housefly, Musca domestica Linnaeus, 1758. Their effects on a major parasitoid of houseflies; Muscidifurax raptor Girault & Sanders, 1910 were also investigated. Both essential oils were found to have significant insecticidal activity against larvae and pupae of houseflies. The LC50 of C. sinensis and M. pulegium essential oils were for larvae 3.93 and 0.71 ml/cm2, and for pupa 0.41 and 0.23 ml/cm2, respectively. Surprisingly, the parasitoids were less affected by plant-applied essential oils as compared to houseflies. After 24 and 48 hours of exposure, the LC50 for C. sinensis and M. pulegium essential oils was found to be 71.2 and 52.6 ml/cm2 and 45.2 and 37.6 ml/cm2, respectively. Overall, this experiment indicated that low concentrations of essential oils were found to have a significant effect on houseflies, but not parasitoids. Thus, it can be used in combination in Integrated Pest Management (IPM) programs to provide effective results.